Ensuring the technological independence of oil and gas companies using patent analytics on the example of companies producing liquefied natural gas - A. T. Volkov; R. E. Shepelev (Вестник университета, 2023)
The article analyzes technological development of the oil and gas industry in Russian Federation under international sanctions, as well as the directions of technology development and equipment production. The article purpose is to identify ways to achieve technological sovereignty in the industry. Patent statistics and construction of patent landscapes is considered as a method of choosing the direction of technological development. The study object is Russian oil and gas companies, while the main attention is paid to companies producing and distributing liquefied natural gas. The study subject is application of patent statistics for identifying trends and directions of technological development of the industry. The study result is determination of industry leaders, and the most promising areas of research in the field of means and methods of liquefied natural gas transportation, methods of its liquefaction or curing, as well as storage equipment. The article draws conclusions about the most promising technologies and patent trends, such as the creation of mobile plants for production of liquefied natural gas , including the construction of its own fleet of gas carriers and floating plants for the gas liquefaction to provide access to the infrastructure of offshore fields. In addition, for rapid development of new markets, the use of floating terminals for regasification is proposed. Approaches to assessing the innovation activity and competitiveness of companies have been considered.